Why does exercise terminate at the maximal lactate steady state intensity?. Issue 10 (10th December 2007) - Baron, B; Noakes, T D; Dekerle, J; Moullan, F; Robin, S; Matran, R; Pelayo, P
Abstract : Objective: The purpose of this study was to measure physiological responses during exercise performed until exhaustion at the exercise intensity corresponding to the maximal lactate steady state (MLSS) in order to determine why subjects stopped. Methods: Eleven male trained subjects performed a test at MLSS on a cycle ergometer until exhaustion. Results: Time to exhaustion was 55.0 (SD 8.5) min. No variation was observed between the 10th and the last minute for arterial pyruvate, bicarbonate, and haemoglobin concentrations, redox state, arterial oxygen pressure, arterial oxygen saturation, osmolality, haematocrit, oxygen uptake, carbon dioxide output, and gas exchange ratio (p>0.05). Arterial lactate concentration and arterial carbon dioxide pressure decreased significantly whereas pH, base excess and the Ratings of Perceived Exertion (RPE) increased significantly (p<0.05). Although respiratory rate, minute ventilation and heart rate increased significantly until exhaustion (p<0.05), values at termination of the MLSS test were significantly lower than values measured during a maximal exercise test (p<0.05). Blood ammonia concentrations rose progressively during the MLSS test. However, there is no known mechanism by which this change could cause peripheral fatigue. Conclusions: Exercise termination was not associated with evidence of failure in any physiological system during prolonged exercise performed at MLSS. Thus the biological mechanisms of exercise termination at MLSS were compatible with an integrative homoeostatic control of peripheral physiological systems during exercise.